2020
DOI: 10.1111/fcp.12567
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential of metformin on valproic acid‐induced autism spectrum disorder in rats: involvement of antioxidant defence system

Abstract: Prenatal exposure to valproic acid (VPA) has been shown to increase the risk of autism in children. This study examined the effect of metformin on VPA‐induced autism spectrum disorders in rats. Pregnant albino rats administered VPA (500 mg/kg, i.p.) or normal saline (10 mL/kg, i.p.; vehicle‐control) on gestational day 12.5. The pups were given metformin (5, 50 or 500 mg/kg, p.o.) or vehicle (10 mL/kg, p.o.) daily from postnatal day (PND) 21–50. Social behaviour, spatial learning/reference memory, repetitive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Improved sociability of our adolescent rats treated with either risperidone or metformin was confirmed by the obviously higher preference to spend time with the novel rat rather than with the object (non-social stimulus). Our results correlate with previous studies (Hara et al 2017 ; Wang et al 2018 ; Ishola et al 2020 ; Román et al 2021 ; Deng et al 2022b ; Elnahas et al 2022 )…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Improved sociability of our adolescent rats treated with either risperidone or metformin was confirmed by the obviously higher preference to spend time with the novel rat rather than with the object (non-social stimulus). Our results correlate with previous studies (Hara et al 2017 ; Wang et al 2018 ; Ishola et al 2020 ; Román et al 2021 ; Deng et al 2022b ; Elnahas et al 2022 )…”
Section: Discussionsupporting
confidence: 93%
“…Mechanisms by which metformin ameliorates the characteristic ASD behavioral phenotypes remains an interesting question. Down rearrangement of mTOR/mTORC1 signaling in the cerebral cortex (Wang et al 2018 ) or cerebellum (Liu et al 2022 ), down-regulation of the pro-inflammatory cytokines (NF-κB, IL-17A, and IL-6) in the hippocampus (Deng et al 2022b ), reestablishment of oxide-antioxidant balance and enhancement of cortical and hippocampal cholinergic activity (Ishola et al 2020 ), selective abundance of some gut microbiota and/or enhanced serotonin production in the colon (Deng et al 2022a ); were all suggested in preclinical models treated with metformin. In similar context, the favorable behavioral effects of risperidone in ASD were explained by its ability to suppress neuroinflammation (Elnahas et al 2022 ), restore redox balance and regulate serotonergic and dopaminergic transmission in the prefrontal cortex and hippocampus (Hara et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports describe the effect of early stressors on this response ( Couto et al, 2012 ; Diehl et al, 2012 ). These studies usually use severe stressors, such as anticonvulsant drugs ( Ishola et al, 2020 ), amphetamine ( Holubová et al, 2018 ), ultrasound exposure ( Abramova et al, 2020 ), maternally induced diabetes ( Huerta-Cervantes et al, 2020 ), gamma exposure ( Pipová Kokošová et al, 2020 ), or chronic changes in maternal diet during gestation ( Bengoetxea et al, 2017 ). Such procedures cause serious cellular alterations in many brain regions, including the hippocampus, and the results found in the MWM may reflect these structural alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested that neonatal metformin treatment is capable of averting some of the classic behavioral symptoms commonly observed in patients with ASD. In addition, a recent study conducted on rats to examine the effect of metformin on valproic acid-induced autism-like behaviors has demonstrated that postnatal treatment with metformin improved the sociability index, spatial learning, and reference memory deficits through the attenuation of malondialdehyde and nitrite levels, AChE activity, and antioxidant enzymes activities in the rat hippocampus and prefrontal cortex [159]. In humans, the clinical studies on the beneficial effects of metformin are controversial.…”
Section: Metforminmentioning
confidence: 99%